Earth-Man Relationship in Islam and Hinduism: A Comparative Study of Eco-Theological Response of Fazlun Majeed Khālid and Ranchor Prime - Sadiqa, Ulfat; Rafi, Amt ul (Al Basirah, 2022)
The relationship between man and earth has been both sacred and tender since time immemorial. This bond is based on the guiding principles enshrined and practiced deftly in all religious scriptures. Islam and Hinduism are unique as having a deep sense of respect and consideration for Earth and its natural resources. Fazlun Majeed Khālid and Ranchor Prime being the contemporary scholars of Islam and Hinduism respectively, attempted to bring religious understandings of earth and the place of human beings on it into the discourse of the present ecological crisis. They shifted the global vision of the earth-man relationship to a religious understanding of ‘self and surrounding'. They tried to solve the current ecological crisis that our planet is facing after the advent of scientific knowledge and technological development in a purely eco-theological dimension. Khālid tries to address these issues from an Islamic understanding of nature while Prime attempts to deal with the ecological crisis from the Hindu faith. Both scholars criticized the anthropocentric value approach of the West and present the Cosmo-centric value approach as an alternative ethical approach to protecting our home planet Earth and its resources. This article presents a comparative analysis of their eco-theological thoughts to sustain an earth-man relationship in the 21st century. Keywords: Earth-man Relationship, Sustainability, Ecological Crisis, Secular Worldview, Anthropocentric, Cosmo-centric, Comparative Analysis.